2002
DOI: 10.1002/ccd.10375
|View full text |Cite
|
Sign up to set email alerts
|

Intracoronary verapamil for reversal of no‐reflow during coronary angioplasty for acute myocardial infarction

Abstract: No-reflow is a frequent observation during direct PTCA for acute myocardial infarction (AMI) and associated with a poor clinical outcome. This study assesses the value of verapamil for reversal of no-reflow during PTCA for AMI. In a consecutive series of 212 direct or rescue PTCAs for AMI, a TIMI flow grade < 3 was observed in 23 patients (10.8%). Ten of these patients had received GP IIb/IIIa antagonists before PTCA. Seven patients with AMI and TIMI grade 3 flow served as controls. All lesions were treated by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(48 citation statements)
references
References 39 publications
2
45
0
1
Order By: Relevance
“…Evidence for a beneficial effect on no-reflow exists for abciximab, adenosine, nicorandil, and nitroprusside. 674,675,680,682,683,685,687,688,690 However, their adoption into clinical practice has depended on their effect on hard clinical endpoints such as infarct size and mortality. These benefits, and consequentially the use of these agents, have been limited.…”
Section: Fondaparinux: Recommendationmentioning
confidence: 99%
“…Evidence for a beneficial effect on no-reflow exists for abciximab, adenosine, nicorandil, and nitroprusside. 674,675,680,682,683,685,687,688,690 However, their adoption into clinical practice has depended on their effect on hard clinical endpoints such as infarct size and mortality. These benefits, and consequentially the use of these agents, have been limited.…”
Section: Fondaparinux: Recommendationmentioning
confidence: 99%
“…Although primary stenting is the most reliable strategy, the no-reflow phenomenon does occur in some patients. Investigators have reported the management of no-reflow, [20][21][22][23] but few preventive therapies for no-reflow in AMI have been described. Recently, Limbruno et al reported the effectiveness and safety of the non-occlusive filter type distal protection device (FilterWire-Ex ® ) during PCI in AMI caused by native coronary obstruction; 24 however, the effects of the filter type protection device for LV function remain uncertain because of the variation in IRAs in that study.…”
Section: Discussionmentioning
confidence: 99%
“…Intracoronary nitroprusside has the advantage of having no hemodynamic side-effects. 49,50 In contrast, intracoronary verapamil can cause bradyarrhythmias, 51,52 but it may also attenuate stunning 53 and contribute to a reduction of infarct size. 54 Also, the half-life of verapamil is longer, and it does not require continuous intracoronary infusion.…”
Section: Kleinbongard Et Al Vasoconstrictor Potential Of Coronary Aspmentioning
confidence: 99%